2012 9th International Conference on Communications (COMM) 2012
DOI: 10.1109/iccomm.2012.6262599
|View full text |Cite
|
Sign up to set email alerts
|

Development of multiresolution hierarchical trees to non-cooperative target recognition

Abstract: To cite this version:Christian Brousseau. Development of multiresolution hierarchical trees to non-cooperative target recognition. MTA Review -Military Technical Academy Publishing House, 2012, XXII (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Previous results [5] has shown that better performances are obtained with a hard clustering algorithm, like K-means, in NCTR applications. Thus, in the next sections, results obtained with the K-means hard partitioning method are only presented.…”
Section: Unsupervised Clustering Of Rcs Databasementioning
confidence: 93%
See 3 more Smart Citations
“…Previous results [5] has shown that better performances are obtained with a hard clustering algorithm, like K-means, in NCTR applications. Thus, in the next sections, results obtained with the K-means hard partitioning method are only presented.…”
Section: Unsupervised Clustering Of Rcs Databasementioning
confidence: 93%
“…Fig.4 presents an example of range profile and its wavelet decomposition computed in four levels. Another work [5] has shown that there is no statistically significant difference in performance of the classifier when different wavelets are chosen. Thus, in the next sections, results obtained with the Haar wavelet are only presented.…”
Section: B Rcs Multiresolution Wavelet Representationmentioning
confidence: 97%
See 2 more Smart Citations
“…A previous work [15] has shown that there is no statistically significant difference in performance of the classifier when different wavelets are chosen. Thus, in the next sections, only results obtained with the Haar wavelet are presented.…”
Section: B) Multiresolution Wavelet Representation Of Rcs Databasementioning
confidence: 94%